Inter - generational Practices - Galina Mihailovna Tsinchenko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Article is devoted to the practice inter - generational interactions. In today’s society, different inter - generational practice, provide systematic and deliberate interaction between elderly and young people. Such practices offer a mechanism to support people of different generations. Inter - generational practices to meet the needs in contacts between generations, break down the barriers between age groups. Practice among the generations affect many social, economic and political factors